3D Cell Culture: Techniques For and Beyond Organoid Applications - Sumbalova Koledova, Zuzana (Methods in molecular biology, 2024)
In the rapidly evolving landscape of cell biology and biomedical research, three-dimensional (3D) cell culture has contributed not only to the diversification of experimental tools available but also to their improvement toward greater physiological relevance. 3D cell culture has emerged as a revolutionary technique that bridges the long-standing gap between traditional two-dimensional (2D) cell culture and the complex microenvironments found in living organisms. By providing conditions for establishing critical features of in vivo environment, such as cell-cell and cell-extracellular matrix interactions, 3D cell culture enables proper tissue-like architecture and differentiated function of cells. Since the early days of 3D cell culture in the 1970s, the field has witnessed remarkable progress, with groundbreaking discoveries, novel methodologies, and transformative applications. One particular 3D cell culture technique has caught the attention of many scientists and has experienced an unprecedented boom and enthusiastic application in both basic and translational research over the past decade - the organoid technology. This book chapter provides an introduction to the fundamental concepts of 3D cell culture including organoids, an overview of 3D cell culture techniques, and an overview of methodological- and protocol-oriented chapters in the book 3D Cell Culture.
Keywords: techniky 3D buněčné kultury; Cell Culture Techniques, Three Dimensional; organoidy; Translational Research, Biomedical; Cell Culture Techniques; Biomedical Research; translační biomedicínský výzkum; biomedicínský výzkum; buněčné kultury; Organoids